Análise comparativa da Distribuição dos Leitos de UTI-SUS nos Estados Brasileiros - Barbosa, Ana Nicolle Mendes (Brasil, 2025)
This study aims to analyze the evolution and distribution of UTI-SUS beds per 10,000 inhabitants in the different macro-regions and Brazilian states between 2006 and 2024, understanding the transformations in three specific periods: pre-pandemic, pandemic and post- pandemic. Through the temporal analysis and data that indicate the problem inserted in the initial years of this research, the gap is found through the occupancy of ICU beds due to the Covid-19 pandemic. The research methodology for this study was through a literature review of literary works from the last five years, delimited in the period from January 2020 to September 2024, which occurred through specific databases in the health area and multidisciplinary, such as PubMed, Lilacs, Medline, SciELO and others. For the other delimitations of data collection and analysis, the eligibility criteria were applied, better detailed in the methodological section of this article. To this end, we seek to obtain information that allows an approximation of the conditions of access to public and private services, considering the need for the health system to provide fast and efficient care during the pandemic in ICU beds. Likewise, the objective of this research is given through an analysis of evidence on the supply and demand of health services and their consequent occupancy in beds in hospital units.